(untitled) (Al-Academy, 2022)
Showing animal shapes is one of the primary topics since the discovery of cave drawings, with semantic discourses, as they appeared in the ancient civilization of Iraq, with their discourse and intellectual structure, and their reflections on their plastic achievements. The research deals with three topics: the first (an introduction to the concept of discourse), the second: (the historical roots of animal forms), and the third (the manifestation of animal forms and their discourse, in Mesopotamia). Mesopotamian fauna and its concepts? What are the?, Its importance was also represented in: the presence of animals and their semantic and conceptual discourse, especially the sculptures (the lion and the bull), with the aim of revealing the statement of the discourse and its relational and intellectual impact on them, then the indicators of the cognitive framework, analyzing the research samples and presenting its results, summarized by showing the discursive relations conceptual, employing the presence of the Mesopotamian sculptural forms of the lion and the bull